The hydrodynamic drag during the gliding in swimming - Marinho, D.; Sousa, L.; Reis, V.; Alves, F.; Vilas-Boas, J. P.; Moreira, A.; Silva, A.; Rouboa, A. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The gliding phase during starts and turns can play an important role in the final performance in swimming races (Lyttle et al., 2000). Therefore, the aim of this study was to analyse the effect in the drag coefficient (CD) of the use of two distinct ventral positions during the gliding in swimming, using Computational Fluid Dynamics (CFD). Methods The CFD analysis consisted in the use of a threedimensional (3D) mesh of cells that simulates the flow around the considered domain. We used the k-epsilon turbulent model (Moreira et al., 2006) implemented in the commercial code fluent and applied to the flow around a 3D model of a male adult swimmer in two gliding situations, both in ventral position: with the arms extended at the front and with the arms placed aside the trunk. The simulations were applied to different flow speeds, between 1.60 m/s and 2.00 m/s to both situations and the CD was computationally calculated to each one of the applied speeds. The swimmer model was 1.80 m high and 0.50 m width. Results In the position with the arms extended at the front, speeds of 1.60, 1.70, 1.80, 1.90 and 2.00 m/s produced, respectively, CD values of 0.96, 0.95, 0.86, 0.85 and 0.84. In the position with the arms aside the trunk, speeds of 1.60, 1.70, 1.80, 1.90 and 2.00 m/s produced, respectively, CD values of 1.65, 1.56, 1.53, 1.52 and 1.47. Discussion In both gliding positions the swimmer CD decreased with the speed increasing. The inverse relationship between the CD and the speed found in the present study seems to correspond to what happens in experimental situations in the human body totally submersed (Jiskoot and Clarys, 1975; Lyttle et al. (2000). In our opinion, the use of 3D instead of a 2D model seems to be an important step to the decrease in the gap between the experimental and the computational data. This work allowed to verify that the gliding position with the arms extended at the front presented lower CD values than the position with the arms placed aside the trunk. This body position, with the arms at the front, is mostly accepted by the swimming technical and scientific communities as the most hydrodynamic one, being called the streamlined position (Guimarães and Hay, 1995). The adoption of this position during the gliding after starts and turns must be a main concerning in the swimmers training.